Understanding identity and positioning for responsive critical literacies. (4th May 2019) - Asher Golden, Noah; Zacher Pandya, Jessica
Abstract: This article revisits questions on the utility of identity in literacy studies. Following a review of the range of conceptions of identity and framings of its uses, we argue that identity-as-position is needed as a pragmatic tool in the field of literacy studies, and grounds responsive critical literacy practices. Drawing on a narrative analysis case study, we develop propositions that show how literacies research and education might support learners' desired identity enactments. Specifically, we describe three frames for theories of identity enactment, reviewing opportunities for knowledge-building within each frame. We reflect on the possibilities for research through these frames in light of a narrative shared by Diego, a 20 year-old seeker of a High School Equivalency degree in New York City. Finally, we offer propositions for researchers in literacy studies to follow (or argue against) as they build knowledge on participants' positions and desires. We advocate for the utility of understanding identity-as-position to address issues of equity through the possibility of responsive critical literacy practices and desire-centered research methodologies.